Local Wisdom and Sustainable Fisheries Management in Aceh Province: Customary Law Perspective (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Fishery resources, especially captured fisheries, because they are open access, if not managed properly in their use or over exploited, can have an impact on causing the extinction of fishery resources. World fisheries' consumption continues to increase while capture fisheries production continues to decline. This can be threaten world food security, especially in the fisheries sector. Aceh Province is a province surrounded by the ocean and have large fishery capture. Illegal, unreported and regulated fishing which threatens the sustainability of fisheries resources in the region. On the other hand, the Aceh fishing community has a Laot Traditional Institution known as Panglima Laot which, based on local wisdom, has been able to preserve fisheries resources to this day. Based on the description above, the problem is What is the role of local wisdom in sustainable fisheries' management in Aceh Province? This research is normative legal research carried out by searching for and finding legal sources that are relevant to the subject being studied. The research results show that Aceh Province has the authority to carry out sustainable fisheries' management both in law and the Aceh Qanun which regulates this. Apart from being carried out by the government, management is also carried out by the Panglima Laot traditional institution which has its own system, structure and rules, especially for fishing at sea. These local wisdom values have the values of justice, togetherness and sustainability. This institution plays an important role in resolving various disputes that occur between fishermen. There are regulations that can fill in the national and international legal rules that apply in terms of fishing, which, is implemented effectively, can increase the guarantee of the sustainability of fisheries resources that will remain sustainable.
Keywords: Local Wisdom; Sustainable Fisheries; Customary Law